An integrated gas supply reliability evaluation method of the large-scale and complex natural gas pipeline network based on demand-side analysis. (August 2021) - Yu, Weichao; Huang, Weihe; Wen, Yunhao; Li, Yichen; Liu, Hongfei; Wen, Kai; Gong, Jing; Lu, Yanan
Highlights: A demand-side analysis-based gas supply reliability evaluation method is proposed. The fluctuation characteristics and the effect of user importance is considered. The method is applied to a real natural gas pipeline network located in China. The significance of the demand side in the gas supply reliability is elaborated. Abstract: The fluctuation characteristics of the gas demand and the effect of the user importance are usually ignored in previous gas supply reliability research. With the intent of overcoming these deficiencies, an integrated method based on the demand-side analysis is proposed in this study to assess the gas supply reliability of the large-scale and complex natural gas pipeline network. The method is composed of the establishment of the indicator system, the demand-side analysis, the estimation of the unit failure probability, and the calculation of the gas supply. Among them, the demand-side analysis focuses on the market demand forecasting and user importance research. Moreover, the coupling effect of the user importance, the hydraulic and pressure constraints, and the unit failure on the gas supply calculation is considered. Furthermore, a real natural gas pipeline network located in China is applied to confirm the feasibility of the method. According to the evaluation results of the gas supply reliability, the weakest nodes and key links of the natural gas pipeline network are identified, and the suggestions to improve the gas supply reliability are proposed as well. At last, the significance of the demand side in the gas supply reliability is elaborated and validated.